Implementasi Perancangan Sistem Informasi Akuntansi Penjualan Perumahan Pada CV Mitra Alam Sejahtera - Reza Maulana; Yulia; Basilia (LPPM Universitas Bina Sarana Informatika, 2022)
The development of science and technology has accelerated, one of which is the economy. Currently, information technology plays an important role in facilitating the completion of a job, increasing employee activity so that they have good skills or abilities. This is evidenced by the number of companies that use computerized systems as a tool to facilitate work and make the company has high quality. The problems faced by CV Mitra Alam Sejahtera have not been used a computerized system. Therefore, a residential sales accounting information system was created to help solve the problem of CV Mitra Alam Sejahtera. The use of the system has also facilitated operational activities on CV Mitra Alam Sejahtera such as being able to manage register data, transaction data, housing report data, housing data, event news and monitoring reports. The system can also produce reports needed by CV Mitra Alam Sejahtera such as home purchase data reports, housing data reports, which become obstacles while still using manual methods.